Current use of sensor-based measurements for paraplegics: a literature review - Benning, Nils-Hendrik; Hagen, Niclas; Knaup-Gregori, Petra (Digital personalized health and medicine, 2020)
Sensors are used in many fields to measure physical phenomena, often on mobile persons. Paraplegia is a disease with a massive impact on the ability to move, so patients show changes in walking behaviour or are even wheelchair users. It is unclear how sensors can be used with paraplegics to generate valid data for research. In the ParaReg project, such data shall be integrated with a medical register. In this paper, we elaborate current approaches for sensor measurements that might serve as an additional data source for ParaReg with the help of a literature review. We queried IEEE Xplore and MEDLINE to find publications that describe the current use of sensors for patients with paraplegia. The retrieved publications were screened for eligibility by two reviewers independently. To ensure reproducibility, we conducted an initial alignment. All publications were assessed based on their abstract. Inclusions were analysed for their major topic, and we proposed categories, which were statistically described afterwards. We retrieved 685 publications in total and included 287 publications in our analysis. The categories we found are: "diagnostic sensor tools for clinical environments", "seating position analysis", "functional electrical stimulation (FES) / neuroprosthesis control", "seating position analysis", "control systems for devices" and "assessment of physical activity". "FES / neuroprosthesis control" shows most publications and the highest publication rate in history, followed by "assessment of physical activity".
Gesehen am 24.06.2020